2011
DOI: 10.1200/jco.2010.34.5520
|View full text |Cite
|
Sign up to set email alerts
|

Impact of KRAS and BRAF Gene Mutation Status on Outcomes From the Phase III AGITG MAX Trial of Capecitabine Alone or in Combination With Bevacizumab and Mitomycin in Advanced Colorectal Cancer

Abstract: KRAS gene mutation status was neither prognostic for OS nor predictive of bevacizumab outcome in patients with advanced CRC. BRAF gene mutation status was prognostic for OS but was not predictive of outcome with bevacizumab.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
129
4
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 204 publications
(146 citation statements)
references
References 25 publications
10
129
4
3
Order By: Relevance
“…Hurwitz et al observed no apparent association between the improved PFS and KRAS status for patients treated with bevacizumab and irinotecan and fluoropyrimidine chemotherapy (28). More recently, the MAX study confirmed that KRAS mutation status was neither prognostic for OS nor predictive for bevacizumab outcome in patients with advanced CRC (29). These two studies analyzed the role of KRAS mutations in patients treated with irinotecan-or mytomicin-based chemotherapy plus bevacizumab, which are not the most commonly used chemotherapeutic regimens worldwide in the first-line setting.…”
Section: Discussionsupporting
confidence: 65%
“…Hurwitz et al observed no apparent association between the improved PFS and KRAS status for patients treated with bevacizumab and irinotecan and fluoropyrimidine chemotherapy (28). More recently, the MAX study confirmed that KRAS mutation status was neither prognostic for OS nor predictive for bevacizumab outcome in patients with advanced CRC (29). These two studies analyzed the role of KRAS mutations in patients treated with irinotecan-or mytomicin-based chemotherapy plus bevacizumab, which are not the most commonly used chemotherapeutic regimens worldwide in the first-line setting.…”
Section: Discussionsupporting
confidence: 65%
“…RAS mutations represent the only, molecular, predictive biomarker approved for clinical use, while their prognostic role is still debated. Several randomized studies have shown no significant survival differences between KRAS mutated and KRAS wild-type, CRC patients, independently of anti-EGFR therapy (Price et al, 2011;Hecht et al, 2009;Kastrinakis et al, 1995;Russo et al, 1998;Tol et al, 2010), while others have demonstrated a prognostic role of KRAS in advanced disease (Richman et al, 2009;Maughan et al, 2011;Tejpar et al, 2012). BRAF mutations have been described in about 10% of primary CRC, representing a well-known negative prognostic factor, associated with worse survival outcomes, regardless of any treatment received (Ahn et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…[3] The mechanism for the poor prognosis is poorly understood, and it is unclear at what point in the aCRC treatment pathway that Bmutant outcomes diverge from wildBtypes; whilst OS is uniformly poor, less impact is seen with PFS compared with wildBtypes. [4,5] It has been hypothesised that poor outcomes are secondary to intrinisc chemoresistance but there is a paucity of data describing the outcomes of Bmutant aCRC with chemotherapy alone, particularly beyond the firstBline. This is particularly important as B mutant patients have questionable benefit from antiBepidermal growth factor receptor (antiBEGFR) therapies [6] and Btargeted strategies have yet to make clinical impact in aCRC.…”
Section: Introductionmentioning
confidence: 99%